Evaluation of antibacterial activity of Bacillus velenesis 21-128 against Xanthomonas campestris pv. Campestris - Moon Joo Kim; Eun-Jae Park; Bori Lee; Hyun-Jae Jang; Jongmin Ahn; Ji-Hye Kim; Young Ho Kim; Bong-Sik Yun; Seung Woong Lee (Biological Control)
Xanthomonas campestris pv. campestris (Xcc) is a gram-negative bacterium that causes black rot, a disease that significantly reduces cruciferous crops yields. Crop production is facing environmental and health challenges associated with the use of synthetic chemicals, highlighting the need for effective biological control agents as sustainable alternatives. In this study, we isolated and characterized the Bacillus velezensis 21–128 strain for antimicrobial activity against Xcc using pot experiments and various enzymatic activity assays. We used ultra-performance liquid chromatography and quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF-MS) analysis to confirm the presence of lipopeptides, including surfactins in the ethyl acetate extract from Bacillus velezensis 21–128. Four types of surfactins—C13, C14, C15, and C16—were identified by mass fragmentation analysis. Further, we used a combination of separation methods, including HP-20 column chromatography, MPLC, and semi-preparative HPLC to isolate and purify the identified surfactins. The purified surfactins were compared with standard substances using HPLC and identified through comparative analysis with LC-MS data. Lastly, we evaluated the antimicrobial activity of the isolated surfactins against the Xcc strain, and determined the minimum inhibitory concentration values for the total surfactin group, G2, G3, G4, and G5. These results suggest that the Bacillus velezensis strain 21–128 could serve as a biological control agent against Xcc and could be a promising strategy against black rot in cruciferous crops.